2018
DOI: 10.3390/f9050263
|View full text |Cite
|
Sign up to set email alerts
|

High Mortality and Low Net Change in Live Woody Biomass of Karst Evergreen and Deciduous Broad-Leaved Mixed Forest in Southwestern China

Abstract: Repeated observation based on large permanent monitoring plots is a key method for directly understanding forest regeneration dynamics. Karst forests grow slowly in adverse habitats and possess a special regeneration mode. However, no data can support these properties because no repeated observations have been performed. The mortality, recruitment, and net change in live woody biomass (NPP lw ) of a karst evergreen and deciduous broad-leaved mixed forest in Central Guizhou Province, Southwestern China, were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…Fig. 2 shows that the mortality of the trees with small DBH was the highest and with medium DBH was the smallest, which is consistent with the findings obtained from the evergreen and deciduous broad-leaved mixed forest in the Karst region of southwest China (Liu et al 2018) and the Tiantong National Forest Park (Wu et al 2014). Note that the trees with small DBH also showed the highest recruitment rate.…”
Section: Analysis Of Recruitment and Mortalitysupporting
confidence: 86%
“…Fig. 2 shows that the mortality of the trees with small DBH was the highest and with medium DBH was the smallest, which is consistent with the findings obtained from the evergreen and deciduous broad-leaved mixed forest in the Karst region of southwest China (Liu et al 2018) and the Tiantong National Forest Park (Wu et al 2014). Note that the trees with small DBH also showed the highest recruitment rate.…”
Section: Analysis Of Recruitment and Mortalitysupporting
confidence: 86%
“…For example, the largest biomass increase in the world occurred in the South China karst region between 1999 and 2012 [10]. Other studies reported the biomass in typical karst ecosystems, or along vegetation restoration areas based on surveys of small plots [2,6,[11][12][13][14]. However, no biomass investigations have been conducted on a local scale in the karst region, especially in forests.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the degraded land has seen a shift from cropland or abandoned bare land to forest or other secondary vegetation. Several studies have examined the aboveground biomass in karst regions, including biomass change with vegetation restoration (Cheng et al, 2015; Liu et al, 2016, 2018; Tong et al, 2018). However, our current knowledge of belowground fine root biomass is considerably more limited than that of aboveground biomass in karst regions, and the effects of ecological restoration on fine root biomass have not been evaluated in detail in this fragile ecosystem.…”
Section: Introductionmentioning
confidence: 99%